P‐140: Lamination Technology for Flexible AMOLED. Issue 1 (May 2017) - Hsu, Tsi-Hsuan; Yu, Kai-Yu; Lai, Yen-Huei; Wang, Wan-Tsang; Lin, Yu-Hsin
Abstract : The development of next generation display is toward to the form of novel curved display or flexible display to final users. Due to the characteristic of flexibility, the active matrix organic light‐emitted diode (AMOLED) is suitable to manufacture of these types of display. By laminating process, the AMOLED can be bonded onto the curvature glass to form a curved display or bonded onto the flexible substrate to form a flexible display. In this article, the technical trend and the development of lamination technology are demonstrated. Two types of laminator are showed, the roller type and air bag type, in which the former possess higher accuracy and lower tact time than air bag type. To meet the requirement of manufacture narrow border display and mass production, the equipment with high accuracy and low tact time are necessary. We also showed the method to laminate a curved display and showed the solution to overcome the problem beyond lamination.